2022
DOI: 10.1038/s41598-022-05937-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and estrous-cycle dependent dorsal hippocampal phosphoproteomic changes induced by low-dose ketamine

Abstract: Numerous emotional and cognitive processes mediated by the hippocampus present differences between sexes and can be markedly influenced by hormonal status in males and females of several species. In rodents, the dorsal hippocampus (dHPC) is known to contribute to the rapid antidepressant actions of the NMDA receptor antagonist ketamine. We and others have demonstrated a greater sensitivity to the fast-acting antidepressant ketamine in female versus male rats that is estrogen- and progesterone-dependent. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…For example, while one study showed that the basal and lateral parts of the amygdala show greater inhibition during low estradiol phases (diestrus) and high estradiol phases (proestrus), respectively (Blume et al, 2017), another indicated that GluR1 and GluR2/3 expression is not changed by gonadal hormone manipulations in either sex, though other sexually dimorphic brain regions like the hypothalamus did show upregulation of these receptors following hormone replacement with either testosterone in males, or estradiol in females (Diano et al, 1997). Interestingly, the enhanced effects of ketamine in females appear to be mediated by ovarian hormones (Dossat et al, 2018;Saland et al, 2022), and estrogen plus ketamine or its metabolites ((2R,6R)-HNK and (2S,6S)-HNK) had additive effects on increasing Gria1-4 expression, suggesting that estradiol interacts with AMPA receptors to enhance the effects of ketamine (Ho et al, 2018). This finding may shed light on a potential mechanism of the therapeutic potential of ketamine in treating depression in females, though further studies in neurons is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while one study showed that the basal and lateral parts of the amygdala show greater inhibition during low estradiol phases (diestrus) and high estradiol phases (proestrus), respectively (Blume et al, 2017), another indicated that GluR1 and GluR2/3 expression is not changed by gonadal hormone manipulations in either sex, though other sexually dimorphic brain regions like the hypothalamus did show upregulation of these receptors following hormone replacement with either testosterone in males, or estradiol in females (Diano et al, 1997). Interestingly, the enhanced effects of ketamine in females appear to be mediated by ovarian hormones (Dossat et al, 2018;Saland et al, 2022), and estrogen plus ketamine or its metabolites ((2R,6R)-HNK and (2S,6S)-HNK) had additive effects on increasing Gria1-4 expression, suggesting that estradiol interacts with AMPA receptors to enhance the effects of ketamine (Ho et al, 2018). This finding may shed light on a potential mechanism of the therapeutic potential of ketamine in treating depression in females, though further studies in neurons is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few studies to rely on, it seems the difference in response to ketamine between men and women as well as women premenopause and postmenopause is slight ( Coyle and Laws, 2015 ; Freeman et al, 2019 ). However, preclinical studies fail to replicate all the findings of clinical studies and have reported sex-specific and estrous cycle–specific differences in ketamine’s antidepressant effect, relying on behavioral despair to measure depressive-like behaviors ( Carrier and Kabbaj, 2013 ; Franceschelli et al, 2015 ; Sarkar and Kabbaj, 2016 ; Dossat et al, 2018 ; Ponton et al, 2022 ; Saland et al, 2022 ). Nevertheless, most preclinical studies have not used animal models of depression ( Ponton et al, 2022 ), which could be a potential deviation from real life and a source of discrepancies.…”
Section: Introductionmentioning
confidence: 99%